Urine SERPINC1/ORM1 as biomarkers for early detection of lupus nephritis in MRL-lpr mice - Kim, Young-Eun; Lee, Eun-Ju; Kim, Kyunggon; Kim, Do Hoon; Jeong, Mi Ryeong; Yu, Jiyoung; Hong, Seokchan; Lee, Chang-Keun; Yoo, Bin; Kim, Yong-Gil (Frontiers in Immunology, 2023)
Background. To evaluate the usefulness of urine SERPINC1 and ORM1 as biomarkers for early detection of lupus nephritis (LN).Using proteomics, we screened for potential urine biomarkers that differentiate LN from systemic lupus erythematosus (SLE) patients without nephritis. In addition, urine levels of target biomarkers were measured by ELISA in 13-and 23-week-old MRL-lpr (murine model for LN) and MRL/MpJ mice. Histological analysis was also performed on the kidneys of 23-weekold mice.Results. Urine SERPINC1 and ORM1 were elevated in SLE patients with newly diagnosed LN compared with SLE patients without LN (SERPINC1, AUC=.892, P<.001; ORM1, AUC=.886, P<.001). Levels of urine SERPINC1 and ORM1 were also significantly higher in MRL-lpr mice than in MRL/MpJ mice at 13 and 23 weeks (SERPINC1: p<.01 and p<.001 at 13 and 23 weeks, respectively; ORM1: p<.01 at 13 and 23 weeks). In contrast, a significant difference in urine albumin between the two groups was only observed at 23 weeks (p<.001) not at 13 weeks (p=.83). Regarding the kidney pathology of MPL-lpr mice, urine ORM1 and urine albumin, but not urine SERPINC1, were positively correlated with the activity index (ORM1, rho =.879, p<.001; albumin, rho =.807, p=.003) and chronicity index (ORM1, rho =.947, p<.001; albumin, rho =.869, p<.001).We propose that urine SERPINC1 and ORM1 are novel biomarkers for early LN.